Removal of Ammoniacal Nitrogen, Colour and Suspended Solids from Leachate using Aerated Electrochemical Coagulation (AEC) Under the Influence Factors of Electrolyte Concentration and Aeration Rate - Iwan Kurniawan, Azra Batrisyia; Mohd Zin, Nur Shaylinda; Mohamad Zailani, Laila Wahidah (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
In this study, aerated electrochemical coagulation (AEC) was used to treat leachate. This study was conducted to determine the best conditions for the AEC method to remove ammoniacal nitrogen, colour and suspended solids from leachate. Electrolyte concentration and aeration rate were the variable operating parameters of this study. Al and Fe electrodes were aerated with an air pump, and polyaluminium chloride (PAC) was added simultaneously to the leachate sample. The optimum value obtained from the AEC was 60ml of electrolyte concentration and an aeration rate of 1.0 L/min. Based on the optimum conditions, the experimental results removed 38%, 93%, and 95% of ammoniacal nitrogen, colour, and suspended solids, respectively. This indicates that the AEC method enhanced the removal of ammoniacal nitrogen, colour and suspended solids from leachate. However, only suspended solids comply with the effluent standard.